Universal design and accessibility: towards sustainable built environment in Malaysia - Abdul Rahim, Asiah; Zen, Ismawi; Abd Samad, Nur Amirah; Che Rahim, Che Raiskandar (IOS Press BV, 2014)
An overview about the present status of the facilities, awareness and research related to Universal Design in Malaysia since its independence in 1957. For the last 10 years, Malaysia has shown exponential growth in every aspect, and Malaysia government has given numerous supports towards attending the needs of disadvantaged groups including women, children, single parents, elderly and Persons with Disabilities (PwDs). Many standards, regulations, code of practice and guidelines have been developed to have good accessibility, connectivity, usability and seamlessness in built environment. Recently, various groups, including professionals in the building industry have implemented universal design and accessibility in their projects and development. The methodology applied includes table research, observation and access audit at several case studies of public buildings in Putrajaya. KAED Universal Design Unit (KUDU) of International Islamic University Malaysia was formed with the intention to promote the application of universal design in the built environment and product design, as well as to disseminate research findings through international conferences, symposiums, workshops and product competitions. Universal Design is offered as a subject in IIUM Architecture programme, to instil graduates in understanding of the concept of ‘barrier free’, ‘design for all’, ‘inclusive design’ and ‘universal design’ and their application.